Istorietta troiana con le Eroidi gaddiane glossate Studio, edizione critica e glossario - Barbieri, Luca; D'Agostino, Alfonso (Ledizioni, 2018)
Written as a knight between the 14th and 14th centuries and placed on the ridge between the "medium" and "art" prose, the Trojan Istorietta, anonymous and partial version of the third prose editorial of the Roman river Troy de Benoît de Sainte-Maure (ca. 1165), narrates, with emotional significance and stylistic conciseness, a part of that story that had been constituted in the Latin Middle Ages by merging the stories of Darete Frigio and Ditti Cretese and revitalizing them, in the French world, in the light of sensitivity of the XII century. The suggestions of the classical myth, filtered by a typical actualizing attitude, let slip the aspiration to ideals of beauty (Elena), of strength (Achille, Ettore) and courtesy (the city of Troia) capable of attracting a municipal public that aspires to an educational and cultural elevation.
Description based on print version record.
KU Open Services
Keywords: Literary Criticism / European / Italian; Literature -- History and criticism; Electronic books